Auditoría de gestión y su incidencia en los procesos internos de la unidad educativa pcei blaise pascal cantón quevedo. Año 2023 - Palma Carbo, Katherine Michell (2025)
The main objective of this research project is to evaluate the impact of management auditing on the internal processes of the Blaise Pascal Canton Quevedo Educational Unit (PCEI) during 2023. The research was developed using a mixed methodological approach, combining qualitative and quantitative techniques to obtain a comprehensive view of institutional performance. Management indicators were applied to measure the efficiency and effectiveness of the processes. Among the main results, it is highlighted that 89.28% of internal processes were executed within the established timeframe, albeit with a deviation of 10.72%. Only 53.57% of administrative processes have been automated, reflecting a technological gap of 46.43%. Regarding the indicator for responding to student requests, 90% compliance was achieved. Likewise, the annual training plan was executed 66.67%, demonstrating a need to strengthen ongoing staff development. In terms of institutional effectiveness, it was found that 92.30% of staff were familiar with the institutional mission and vision. Furthermore, only 60% of internal communication channels were used effectively, and preventive maintenance was carried out in only 66.67%. Furthermore, the internal control assessment, applied under the COSO I model, yielded a moderate confidence level of 60.80% and a low risk level of 39.20%. The findings were organized into a matrix and integrated into the final management audit report. The results of this project seek not only to improve internal processes but also to establish a sustainable monitoring and evaluation system that strengthens the institution's operational and strategic capacity.